Nitrogen NMR shieldings of 2-amino-5-nitro-6-methylpyridines. Issue 4 (1997) - Palasek Palasek, B. B.; Puszko Puszko, A. A.; Biedrzycka Biedrzycka, Z. Z.; Sicinska Sicinska, W. W.; Witanowski Witanowski, M. M.
Abstract : Nitrogen NMR shieldings (chemical shifts) of 2-amino-5-nitro-6-methylpyridine derivatives are assessed from the point of view of substituent-induced effects under conditions where alkyl, aryl, nitro, and nitroso moieties are substituents at the amino nitrogen. The nitro nitrogen shielding reveals only little variation upon varying the substituents, and this seems to indicate that steric hindrance which is likely to force the nitro group out of the plane of the aromatic ring reduces the π -electron conjugation with the latter, and with the amino group as well. On the other side, the pyridine nitrogen shielding shows large effects of substituents at the amino moiety, which suggests a significant conjugation between the ring and the amino group. The latter effects produce a remarkable deshielding of the pyridine nitrogen in the case of nitro and nitroso substituents at the amino group.